Assessment of Medical Service Pricing in China's Healthcare System: Challenges, Constraints, and Policy Recommendations - Wenying Xiong; Yufan Deng; Yufan Deng; Yili Yang; Yili Yang; Yumeng Zhang; Yumeng Zhang; Jay Pan; Jay Pan (Frontiers Media S.A., 2021)
Medical service pricing reform was considered as one of the focuses of China's remarkable health reform. This paper preliminarily assessed the roles of medical service pricing in the context of China's healthcare system. Specifically, we described the potential roles of medical service pricing in China and pointed out relevant challenges that emerged in practice as the result of reform-related activities. Multiple constraint factors that might have induced undesired outcomes were then recognized, including the excessive diversity and specialization of medical services, the price inelasticity of patients' demand, and the inadequate capability of both medical institutions and administrations. Finally, we provided policy recommendations to inform the ongoing medical service pricing reform in China from a long-term perspective.